1999
DOI: 10.1182/blood.v94.2.448
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcome of Young Chronic Lymphocytic Leukemia Patients: A Single Institution Study of 204 Cases

Abstract: A retrospective analysis on chronic lymphocytic leukemia (CLL) patients ≤55 years observed at a single institution was performed with the purpose of characterizing the clinical features and outcome of young CLL and of identifying patients with different prognostic features. Over the period from 1984 to 1994, 1,011 CLL patients (204 [20%] ≤55 years of age and 807 [80%] >55 years of age) were observed. At diagnosis, younger and older patients displayed a similar distribution of clinical features, except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
2
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(101 citation statements)
references
References 30 publications
10
76
2
12
Order By: Relevance
“…In patients with CLL, we found that a 1-yr increase in age led to approximately a 6% increase in the risk of death (when the patients who died from causes other than CLL were excluded from our analysis, a 1-yr increase in age led to a 5% increase in the risk of death). This finding implies that the prognosis of patients with CLL is not only affected by the disease itself but also by associated comorbidities (14). Our results show an evident difference in the OS of the entire group (148 months) from that of patients who died of causes unrelated to CLL (cardiovascular disease, other malignancy and accident; all infections were considered as CLL related in our analysis) (227 months).…”
Section: Prognostic Markers Of Cllmentioning
confidence: 55%
“…In patients with CLL, we found that a 1-yr increase in age led to approximately a 6% increase in the risk of death (when the patients who died from causes other than CLL were excluded from our analysis, a 1-yr increase in age led to a 5% increase in the risk of death). This finding implies that the prognosis of patients with CLL is not only affected by the disease itself but also by associated comorbidities (14). Our results show an evident difference in the OS of the entire group (148 months) from that of patients who died of causes unrelated to CLL (cardiovascular disease, other malignancy and accident; all infections were considered as CLL related in our analysis) (227 months).…”
Section: Prognostic Markers Of Cllmentioning
confidence: 55%
“…About a third of CLL patients are under the age of 60 years and 10-15% are younger than 50 years. In young adults, CLL has no major distinctive features, the prognostic factors are the same as those in older patients and median survival is less than 3 years for young patients with advanced CLL (Mauro et al, 1999). Young patients with poor risk CLL will need aggressive therapy aimed at achieving a cure, as standard treatment with alkylating agents or purine analogues offers a poor outlook.…”
Section: Discussionmentioning
confidence: 99%
“…reviewed 1011 patients with B-CLL, in which 22 patients terminated to RS (2.2%). 12 These patients constituted 18 cases with DLBCL (1.8%) and four cases with HL (0.4%). A different frequency of RS in a younger group from that in an older group was found.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…75 Mauro et al reported 22 patients with RS among 1011 B-CLL, which consisted of 18 cases with DLBCL and four cases with HL. 12 The rate of patients with B-CLL who developed in HL might account for approximately 0.5% of cases. The report of long-term follow-up of patients with B-CLL receiving Fludarabine regimens as initial therapy, which were produced from the same institution to Fayad et al, revealed four cases of RS found in 174 cases of B-CLL (2.3%).…”
Section: Rs Other Than Dlbclmentioning
confidence: 99%
See 1 more Smart Citation